Synergetic effect of piezo-triboelectric mechanism for high-performance nanogenerators. (15th December 2022) - Tayyab, Muhammad; Zhu, Zhiguo; Lu, Hongyu; Ma, Guanyu; Abbasi, Nasir Mahmood; Gu, Dawei; Wu, Bo; Joseph, Yvonne; Gao, Deqing; Wei, Huang
Abstract: The next generation of power sources for wearable electronics is anticipated to be nanogenerators based on triboelectric and piezoelectric mechanisms, which have proven to be effective at converting biomechanical energy into electrical energy. In this work, the piezoelectric and triboelectric effects of modeling clay were deeply explored. It is interestingly found that dry modeling clay possesses increasing β phase crystallinity when wet modeling clay undergoes annealing treatment. Based on the piezoelectric mechanism, the single-layer device of dry modeling clay delivers a power density of 1 W/m 2, 250 times higher than the single-layer device of wet modeling clay. By piezoelectric mechanism, the single-layer device of polystyrene (PS) film delivers a power density of 0.35 W/m 2 . It is amazing that the nanogenerator composed of dry modeling clay and PS double layers achieves a high-power density of 3.75 W/m 2 . Through deep investigation, it is found that a synergetic piezo-triboelectric mechanism takes effect. The piezoelectric effects in each dry modeling clay, the porous structure of the polystyrene film, and the triboelectric effects occurring between the two layers are all involved. It was demonstrated that 200 and 300 commercial LED lights could be powered by the dry modeling clay-based device and the dry modeling clay-PS double layer device, respectively, showing that the devices have the potential to be used for energy harvesting. Graphical Abstract: A synergetic piezo-triboelectric mechanism, including the piezoelectric effect of each individual layer and triboelectric effect between the two layers, contributes to the enhanced power density of the dry modeling clay-PS double layer TENG. ga1 Highlights: Efficiently increasing β phase crystallinity by thermally annealing wet modeling clay. Enhance power density by increasing β phase crystallinity on the base of piezoelectric effect. Achieve high-performance nanogenerators by piezo-triboelectric synergetic effects.